DEVELOPMENT AND EVALUATION OF GEOGEBRA-BASED LEARNING MEDIA TO ENHANCE STUDENTS' CONCEPTUAL UNDERSTANDING OF PARABOLIC MOTION - Jerfi Jerfi; Fibrika Rahmat Basuki (Physics and Science Education Journal (PSEJ), 2026)
Students often experience difficulties in developing a conceptual understanding of parabolic motion because the topic requires the integration of horizontal and vertical motion, mathematical representations, and vector-based reasoning. This study developed and evaluated a mobile GeoGebra-based learning medium integrating conceptual explanations, interactive simulations, formative assessments, and automated feedback. The study employed a research and development approach based on the ADDIE model involving 37 undergraduate students enrolled in a Basic Physics course. Data were collected through expert validation, a conceptual understanding test, and a student-response questionnaire. The developed learning medium demonstrated high validity and practicality based on expert evaluations and student feedback. Students' mean conceptual understanding score increased from 45.14 before instruction to 79.46 after the intervention. A paired-samples t-test indicated a statistically significant improvement (p < .001) with a large effect size 1.58, while the average normalized gain 0.615 indicated a moderate level of learning improvement. These findings demonstrate that the GeoGebra-based learning medium is a valid, practical, and effective instructional tool for enhancing students' conceptual understanding of parabolic motion in Basic Physics courses. However, further studies using controlled experimental designs are needed to confirm its effectiveness relative to other instructional approaches.